Preoperative transhepatic percutaneous external drainage of the bile duct - Lanza, Mario; Torterolo, Edgardo; Rudnitzky, Omar; Corradi, Daniel; Salice, Mario (Cirugía del Uruguay, 1982)
Report on one case of preoperatory transhepatic percutaneous extemal drainage of biliary tract with description of technique employed, its bases and indications. It has Proved a useful procedure for preoperatory decompression; being pennanent and prolongued, involving in this particular case- no accidents; and renders possible an irnprovement of the patient's condicion prior to surgery, thus reducing the high death rate of these operations.